MODEL EVALUASI PEMBELAJARAN STAIN KUDUS (STUDI KASUS SISTEM EVALUASI PEMBELAJARAN DOSEN PRODI MANAJEMEN BISNIS SYARI’AH STAIN KUDUS) (QUALITY, 2017)
The evaluation system is an important part of the curriculum component used to measure achievement of learning objectives. In learning at STAIN Kudus, each lecturer has different models and forms of learning evaluation. This study aims to examine the model of learning evaluation conducted by lecturers in Sharia Business Management Program (MBS) in 2014. As a result, the evaluation system consists of two types, test and non test. In the type of evaluation the test consists of written tests, oral and deeds. In the written test, there is an objective test form and a description test. While non-tests can be done through observation, portfolio, attitude instruments and so on. Evaluation system used by lecturers on MBS STAIN Kudus Prodi in general is a form of written test type description. Although there are some lecturers who use objective writing tests and oral tests.